2016
DOI: 10.24884/0042-4625-2016-175-5-63-68
|View full text |Cite
|
Sign up to set email alerts
|

Application of Graftskin to Accelerate Healing of Ulcers in Diabetic Foot Syndrome

Abstract: Ключевые слова: трофические язвы, сахарный диабет 2-го типа, дермальный эквивалент В в е д е н и е . Сахарный диабет (СД) рассматривается в настоящее время как неинфекционная пандемия, охватившая большинство стран планеты. Еще 20 лет назад численность больных с СД в мире не превышала 130 млн человек. В настоящее время на нашей планете только по обращаемости насчитывается 366 млн больных с СД (7% населения всего мира), причем около 50% из них приходится на наиболее активный трудоспособный возраст 40-59 лет. Учи… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Six studies on cellular skin substitutes reported on reduction in ulcer area, one 166 with the bilayered skin substitute, four with the polymer scaffold/fibroblast skin substitute, [158][159][160][161] and one with the microvascular tissue structural allograft. 165 All of the 4 studies with the polymer scaffold/fibroblast skin substitute [158][159][160][161] and the single study of the microvascular tissue structural allograft 165 demonstrated greater wound area reduction with the use of cellular skin substitutes compared to standard of care.…”
Section: Outcome: Reduction In Ulcer Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies on cellular skin substitutes reported on reduction in ulcer area, one 166 with the bilayered skin substitute, four with the polymer scaffold/fibroblast skin substitute, [158][159][160][161] and one with the microvascular tissue structural allograft. 165 All of the 4 studies with the polymer scaffold/fibroblast skin substitute [158][159][160][161] and the single study of the microvascular tissue structural allograft 165 demonstrated greater wound area reduction with the use of cellular skin substitutes compared to standard of care.…”
Section: Outcome: Reduction In Ulcer Areamentioning
confidence: 99%
“…We included 19 studies comparing negative-pressure wound therapy to standard of care, 46,166,[255][256][257][258][259][260][261][262][263][264][265][266][267][268][269][270][271] which fitted our inclusion criteria, the majority of which were in post-surgical diabetes-related foot wounds. Two were in a mixed population comprising post-surgical and non-surgical wounds, 255,267 and only one in nonsurgical wounds alone.…”
Section: Intervention 8: Negative Pressure Wound Therapymentioning
confidence: 99%
“…241 Overall, the balance of effects was not thought to favour either Rationale: We identified 19 studies which fulfiled our inclusion criteria. 50,152,[244][245][246][247][248][249][250][251][252][253][254][255][256][257][258][259][260] All studies were thought to be at moderate to high risk of bias.…”
Section: Rationalementioning
confidence: 99%
“…Some examples of acellular skin substitutes would be products such as human acellular dermal matrix and bovine collagen dermal matrix where the cells have been removed and the support structure or matrix is left in place. For the systematic review, 7 we found 10 RCTs [146][147][148][149][150][151][152][153][154][155] on cellular products, 13 RCTs 150,156-167 on acellular products, and 5 RCTs [168][169][170][171][172] on autologous skin graft products. Rationale: Although evidence from 10 RCTs [146][147][148][149][150][151][152][153][154][155] suggest that cellular skin substitutes may improve healing and reduce the time to healing in patients with diabetes-related foot ulcers when provided in addition to standard of care, all studies were at high risk of bias due to non-blinding, had high dropout rates and per-protocol analyses.…”
Section: Intervention: Skin Substitutesmentioning
confidence: 99%
See 1 more Smart Citation